Pengaruh Pasar Industri Pada Dampak Oligopoli Terhadap Globalisasi - Ajeng Pangesti Muttaqiina Gusminto; Muhammad Yasin (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Business actors carry out economic activities for profit. Globalization makes many changes in the times, especially in the industrial economy in Indonesia.Digital economy or disruptive innovation raises business competition problems so as not to cause large losses to consumers and other business actors on a large economic scale creating high barriers to market entry due to the positive economy. This research uses qualitative descriptive, descriptive analysis to see the phenomenon of existing events and qualitative research methods based on philosophy as an instrument, Data collection techniques and qualitative analysis emphasize meaning. Oligopoly markets whose structure consists of two or three or even more control the market 70 to 80 percent of all production or selling value around it and emphasize the price determined. The development of the era of business actors utilizing technology is certainly due to globalization which affects industrial markets in each country to abroad. Oligopoly is very influential in industrial markets because of pressure on prices and new ideas from competitors and supported by digital technology hence industrial market activities to retain consumers. In addition to the effect, business actors get large profits due to increasingly sophisticated information technology. The influence of globalization can encourage large companies to innovate their businesses and be able to integrate in the global market.